Effect of Residual Blotong (Sugarcane Filter Cake) as Organic Matter on EarlyGrowth of Sugarcane (Saccharum officinarum L.) in Sandy Media - Ardiansyah, Angga; Kusumawati, Anna; Siregar, Sutan Borohim (Jurnal Biologi Tropis, 2026)
Sandy soil is dominated by macropores, which causes low water-holding capacity and leads to rapid evaporation before plants can absorb the water. Since water availability is a key factor in plant growth and development, especially in supporting the photosynthesis process, improving soil water retention becomes essential. Applying organic matter has been shown to enhance soil physical properties, increase nutrient availability, and improve water retention within the root zone. This study was carried out to examine the effect of organic matter application on the early growth of sugarcane (Saccharum officinarum L.), as well as on soil pH, temperature, and moisture. Conducted from February 14 to June 6, 2023, at the Practice Field of Politeknik LPP Yogyakarta, the research employed a non-factorial Randomized Block Design (RBD) with two treatments, namely soil media with organic matter and soil media without organic matter, each consisting of 30 sugarcane plants of the Bululawang variety established through the bud set method. Parameters observed included plant height, stem diameter, leaf number, soil pH, temperature, and moisture, with data analyzed using a t-test and correlation analysis. Findings revealed that organic matter application significantly increased both plant height and stem diameter relative to the control. Plants grown in organic matter treated soil achieved an average height of 57.11 cm and stem diameter of 0.55 cm, compared to 31.95 cm and 0.45 cm in the control group. Leaf number was likewise greater in the organic matter treatment (4.00 leaves) than in the control (3.09 leaves), though this difference was not statistically significant. Correlation analysis further showed that soil temperature was positively associated with plant growth, whereas soil moisture had a negative correlation with plant height. Taken together, these results indicate that organic matter application improved overall soil conditions and promoted better early vegetative growth in sugarcane.